Effects of Methotrexate Alone or Combined With Arthritis-Related Biotherapies in an in vitro Co-culture Model With Immune Cells and Synoviocytes - Noack, Mélissa; Miossec, Pierre (Frontiers in Immunology, 2019)
Background: Methotrexate (MTX) at low dose is a key drug for rheumatoid arthritis (RA). MTX is widely used alone or combined with biologics or steroids. The aim was to study its effects on cytokine production using an in vitro model with synoviocytes interacting with peripheral blood mononuclear cells (PBMC) to reproduce the interactions in RA synovium. Methods: Activated-PBMC were co-cultured with RA synoviocytes during 48h. A dose-response of MTX was tested and different biotherapies (Infliximab, Etanercept, Adalimumab, Tocilizumab, Abatacept and Rituximab) were added alone or in combination with MTX. Cytokine production (IL-17, IL-6, IL-1β, IFN-γ and IL-10) was measured by ELISA. These results were compared with those obtained with steroids. Results: MTX alone had a modest inhibitory effect on cytokine production compared to steroids. The most effective concentration was one of the lowest, 0.01µg/ml, as for steroids. Infliximab was the most active biotherapy (p≤0.05 for all cytokines) followed by Tocilizumab (p≤0.05 for all cytokines except IL-6). Abatacept and Rituximab had a more restricted effect on cytokines (p≤0.05 for IL-1β and IFN-γ). The combination MTX/biotherapies did not increase significantly the inhibition of cytokine production but some specific inhibitory effects were observed with Infliximab on IL-17 and IL-6, and with Abatacept and Rituximab on IL-1β. Conclusion: Low dose of MTX was at least as effective as high dose. The effects of the combination with biotherapies showed an important level of heterogeneity between the levels of some specific cytokines and the degree of inhibition with drugs.